Historyczne powieści Henryka Sienkiewicza w ocenie współczesnych i ich wartość ponadczasowa - Siatkowska, Ewa (Acta Universitatis Lodziensis. Folia Linguistica, 2016)
In the article, which is a discussion, the author tries to indicate why among many positivists, discussing historical themes, it was Sienkiewicz who won the greatest popularity, how the society felt about historical works of Sienkiewicz and to what extent the work of the historical Nobel Prize winner contributed to the formation of national identity in the Polish society, helping the Poles to survive the period of captivity.